BALANCED SCORECARD DESIGN AS A MODEL FOR MEASUREMENT OF PUSKESMAS PERFORMANCE IN EAST LOMBOK DISTRICT - Saputraji, Erwin; Arni Muhsyaf, Saipul; Bayu Suryantara, Adhitya (Distribusi - Journal of Management and Business, 2024)
The objective of this study is to develop a performance measuring model based on the balanced scorecard framework at the UPT Puskesmas Suela in East Lombok Regency, using the Analytic Hierarchy Process (AHP) technique. This research employed qualitative approaches. Data were gathered with a paired comparison questionnaire employing the Analytic Hierarchy Process (AHP) scale. The performance evaluation of community health centers is conducted using four reference standards, including the financial perspective, community perspective, internal business process perspective, and development and learning perspective. Utilizing this technique for data processing is beneficial in making judgments based on many factors. The research findings indicate that the primary criterion of utmost importance for community health centers is finance, with a weight of 0.465450. The subsequent prioritization criterion is society, assigned a weight of 0.214555. Additionally, both the internal business process criteria and development and learning criteria hold equal significance, each with a weight of 0.112321. Related indicates that Puskesmas as a public sector agency focuses on improving performance on financial perspectives.